Building and annotating a bachelor paper abstract corpus: First findings about Latvian student abstracts - Egle, Baiba; Lele-Rozentāle, Dzintra; Dubova, Agnese; Jēkabsons, Gints (Kalbotyra, 2025)
The paper discusses the problems identified in the early stages of an interdisciplinary project that focuses on the creation of a bilingual abstract corpus of bachelor’s theses from a linguistic point of view. The aim of this paper is to summarize the identified problem cases and to show the perspective of linguistic analysis of the corpus to be formed based on the research of special literature on the abstract types, the methodology of abstract analysis of bachelor’s theses and problems of text creation, as well as the results of the pilot study.From the annotated corpus of texts, 25 Latvian abstracts and their corresponding 25 English translations were randomly selected. The texts were obtained from the Registry of Final Theses of Riga Technical University (RTU) (2023–2024). When looking at the abstracts in correlation with the RTU methodological instructions, it can be established that the text type ‘abstract’ is mentioned and briefly described, but the descriptions and scope of their structure differ between faculties and study programs. In the pilot study, based on the modified models by Swales and Feak (2009) and Hyland (2000/2004) concerning the structure of abstracts consisting of different moves and steps, the abstracts’ text-internal sequence as well as quantitative indicators, such as detailed breakdowns of moves used, the length of an abstract, etc., were determined. Moreover, the relationship between moves forming patterns and the model of moves was adapted to the needs of researching texts written by Latvian students, and problems encountered during the intentional and deliberate annotation of the corpus were identified. These problems are mainly related to the lack of in-depth academic writing courses and the often-overgeneralized style of methodological instructions. The sequence of the moves and steps in the corpus is diverse. As abstracts constitute an internationally standardized text type, it does not seem purposeful to interpret differences in an intercultural context. This study has also found that the editing of abstract translations should be taught to students due to the way these translations are performed. The results of the pilot study show the need for modern academic writing support, which is the focus of further research.